2023
DOI: 10.1002/jcad.12468
|View full text |Cite
|
Sign up to set email alerts
|

Policy effects of the expansion of telehealth under 1135 waivers on intentions to seek counseling services: Difference‐in‐difference (DiD) analysis

Abstract: Practicing counselors swiftly shifted to telehealth after insurance payers changed their policy to cover telehealth counseling under the expansion of telehealth with 1135 waivers, which has led to concerns over the policy effects on clients' continuing counseling service-seeking intentions. To determine if this shift to telehealth was associated with a change in clients' counseling service-seeking intentions while adjusting for unmeasured confounders and time trends, we performed a differencein-difference anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 115 publications
0
1
0
Order By: Relevance
“…These factors enable students to withstand adversities and continue their educational pursuits in challenging scenarios such as during a pandemic (Skalski et al, 2020). Optimism has been associated with resilience in the face of adverse experiences (Uchida et al, 2018), while helpseeking behaviors have been identified as robust predictors of positive student outcomes, including academic achievement (Tinto, 1993;Li et al, 2014;Zhai et al, 2023). However, an optimism bias, defined as the belief that one is less susceptible to negative events compared to others, may paradoxically reduce students' help-seeking behaviors in response to perceived COVID-19 risk and attendant mental health issues (Park et al, 2021).…”
Section: Protective Factorsmentioning
confidence: 99%
“…These factors enable students to withstand adversities and continue their educational pursuits in challenging scenarios such as during a pandemic (Skalski et al, 2020). Optimism has been associated with resilience in the face of adverse experiences (Uchida et al, 2018), while helpseeking behaviors have been identified as robust predictors of positive student outcomes, including academic achievement (Tinto, 1993;Li et al, 2014;Zhai et al, 2023). However, an optimism bias, defined as the belief that one is less susceptible to negative events compared to others, may paradoxically reduce students' help-seeking behaviors in response to perceived COVID-19 risk and attendant mental health issues (Park et al, 2021).…”
Section: Protective Factorsmentioning
confidence: 99%
“…Researchers can conduct quasi-experimental studies to examine the real-world effectiveness of universal PrEP education to provide real-world evidence to further inform clinical practices and public health policies [64,65]. Lastly, qualitative studies can contribute to a richer understanding of how universal PrEP education increases HIV health literacy among diverse clients.…”
Section: Directions For Future Researchmentioning
confidence: 99%